Ethical Prospects
XXVIII, 310 p.
Keywords: Ethical Prospects: Economy, Society and Environment aims to present and summarize new perspectives and leading-edge results in ethics reflecting on interconnected economic, social and environmental issues. The yearbook reports on innovative practices and policy reforms and provides a forum for discussion about groundbreaking theories. The main function of the yearbook is to present ideas and initiatives that lead toward responsible business practices, policies for the common good and ecological sustainability. It seeks form a value-community of scholars, practitioners and policymakers engaged in genuine ethics in business, environmental management, and public policy.